Socialization of Cash Waqf Management in Universities in Malaysia - Riyaldi, Muhammad Haris; Syahrizal, Teuku Muhammad; Halim, Hendra; Othman, Razali Bin; Umuri, Khairil; Sari, Nurma; Nurlina, Eka; Farid; Susanna; Sartiyah; Rani, Dzacky Muharram (PT Inovasi Pratama Internasional, 2024)
This community service activity titled